2015
DOI: 10.1039/c4gc02185a
|View full text |Cite
|
Sign up to set email alerts
|

Biomass-derived porous carbon materials with sulfur and nitrogen dual-doping for energy storage

Abstract: Biomass-derived porous carbon material with sulfur and nitrogen dual-doping exhibits great potential for energy storage devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
208
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 588 publications
(214 citation statements)
references
References 62 publications
5
208
1
Order By: Relevance
“…Our group reported the synthesis of sulfur and nitrogen dual-doped 2D porous carbon materials by carbonizing the shell of broad beans and a further chemical activation, which was simple and easy to handle. [116] The specific capacitance of the as-prepared 2D porous carbon material reached 202 F g −1 and showed a superior cycling performance for supercapacitors at 0.5 A g −1 . Yu et al also developed a 2D porous carbon nanosheets (aCS) by carbonization and chemical activation of biomass cornstalk.…”
Section: Wwwadvsustainsyscommentioning
confidence: 99%
“…Our group reported the synthesis of sulfur and nitrogen dual-doped 2D porous carbon materials by carbonizing the shell of broad beans and a further chemical activation, which was simple and easy to handle. [116] The specific capacitance of the as-prepared 2D porous carbon material reached 202 F g −1 and showed a superior cycling performance for supercapacitors at 0.5 A g −1 . Yu et al also developed a 2D porous carbon nanosheets (aCS) by carbonization and chemical activation of biomass cornstalk.…”
Section: Wwwadvsustainsyscommentioning
confidence: 99%
“…Because N doping can enhance the electronic conductivity and wettability, while O, B, S or P-doping can provide the pseudo-capacitance, enlarge the carbon interlayer distance and increase additional active sites, N, O co-doping [34,122,123,129,138], N, B co-doping [35,147], N, S codoping [81,92,146,148] and N, P co-doping [39,99,149] have been designed to further improve the electrochemical performances of biomass-derived carbon materials. For instance, Sun et al [147] reported a separated N, B co-doped porous graphitic carbon from nitrogencontaining chitosan through coordinating boric acid and Fe catalyst, and followed by ZnCl 2 -activation process.…”
Section: Surface Chemistrymentioning
confidence: 99%
“…Thermal conversion of biomass provides a wonderful opportunity for the sustainable and economic fabrication of carbon nanostructures. [90,91] Therefore, the researchers have great interest in conversion of biomass to 3D carbon materials. In the past decades, some 3D CNF nanostructures were obtained by the carbonization of a variety of cellulose-rich biomass, such as bacterial cellulose (BC), [16,85] raw cotton, [92] and peanut shells.…”
Section: Thermal Transformation Approachmentioning
confidence: 99%